ANALISA EKSEKUSI WAKTU DARI OBJEK AUGMENTED REALITY PADA APLIKASI AUGMENTED REALITY PENGENALAN TEMPAT MEMANCING BATAM - Riwinoto - May Jackson (Politeknik Negeri Batam, 2018)
Augmented reality or in Indonesian commonly called as an additional reality is a technology that combines the objects in three-dimensional and two-dimensional then displayed it to a real world environment. Augmented reality is used for interactive games, presentations, and media promotions. When we used augmented reality, time that requires to display the object is very important, so that users do not have to wait too long for the object to appear. In augmented reality, there are several methods and researchers using marker-based tracking. After testing by calculating the average time that required by every three-dimensional objects and two-dimensional objects, it showed that two-dimensional objects require less time than the three-dimensional objects.